2013
DOI: 10.1038/nmeth.2516
|View full text |Cite|
|
Sign up to set email alerts
|

Whole-rat conditional gene knockout via genome editing

Abstract: Animal models with genetic modifications under temporal and/or spatial control are invaluable to functional genomics and medical research. Here we report the generation of tissue-specific knockout rats via microinjection of zinc-finger nucleases (ZFNs) into fertilized eggs. We generated rats with loxP-flanked (floxed) alleles and a tyrosine hydroxylase promoter-driven cre allele and demonstrated Cre-dependent gene disruption in vivo. Pronuclear microinjection of ZFNs, shown by our data to be an efficient and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
70
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 15 publications
4
70
0
Order By: Relevance
“…Several genome-editing technologies, such as zinc-finger nucleases (ZFNs) [1][2], transcription activator-like effector nucleases (TALENs) [3] and the Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)/CRISPR-associated 9 (Cas9) system [4][5], have been used to produce knockout rat models by generating DNA double-strand breaks (DSBs) followed by non-homologous end joining (NHEJ)-mediated repair. However, the simple knockout strategies have limits for studying genes that are critical for embryogenesis.…”
Section: Dear Editormentioning
confidence: 99%
See 2 more Smart Citations
“…Several genome-editing technologies, such as zinc-finger nucleases (ZFNs) [1][2], transcription activator-like effector nucleases (TALENs) [3] and the Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)/CRISPR-associated 9 (Cas9) system [4][5], have been used to produce knockout rat models by generating DNA double-strand breaks (DSBs) followed by non-homologous end joining (NHEJ)-mediated repair. However, the simple knockout strategies have limits for studying genes that are critical for embryogenesis.…”
Section: Dear Editormentioning
confidence: 99%
“…Conditional gene modification is usually achieved by using the Cre/loxP system to inactivate a loxP-flanked (floxed) allele via Cre/loxP-mediated recombination. A recent report demonstrated that rats carrying a floxed gene can be successfully produced via microinjection of 2 pairs of ZFNs and 2 plasmid donors into fertilized eggs [2]. In comparison with ZFNs or TALENs, CRISPR/ Cas9 provides a simpler way to edit the eukaryotic genome even in a multiplex manner [4][5].…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…In other studies using linear or circular DNA donors, the outcomes have been very variable. In the only previous study of HDR in rats using nucleases (ZFNs), both circular and linear forms generated HDR events (Cui et al 2011;Brown et al 2013). Using ZFNs in mice, two publications showed that both linear and circular DNA generated HDR (Meyer et al 2010;Meyer et al 2012), whereas another publication showed that only the linear, but not the circular form, could result in HDR (Hermann et al 2012).…”
Section: Genome Editing In Rats Using Tale Nucleasesmentioning
confidence: 99%
“…In addition to ZFN, new genomeediting tools such as transcription activator-like effector nuclease (TALEN) [5] and the clustered, regularly interspaced, short palindromic repeats (CRISPR)/CRISPRassociated protein (Cas) system [6] have offered a rapid and efficient means of genome modification in many species. Technologies of ZFN and TALEN have made genetargeting in the rat genome more convenient and practical [7][8][9]. The CRISPR/Cas system is the most recently developed technology for targeted genome modification in mammalian cells, bacteria, zebrafish and mice [10][11][12].…”
Section: Dear Editormentioning
confidence: 99%